New Key Generation and Encryption Algorithms for Privacy Preservation in Mobile Ad Hoc Networks - Amiruddin, Amiruddin; Ratna, Anak Agung Putri; Sari, Riri Fitri (International journal of communication networks and information security, 2022)
Mobile Ad Hoc Networks (MANETs) get widespread applications along with the evolving technologies. However, MANETs are at risk due to the shortage of security mechanisms. In this paper, we propose new algorithms for key generation and encryption for privacy preservation in MANETs. Our key generation algorithm modified Fibonacci sequence by adding scrambling factors to generate random key sequences with required length but incurred low computational overhead, whereas the encryption/decryption algorithm utilizes the One Time Pad (OTP) system by adding scrambling factors for data confidentiality which satisfies the randomness, diffusion, and confusion tests. Simulation of the proposed algorithms was conducted using Matlab and NS-2. Experiment results showed that the proposed algorithms produced random key sequences and random Ciphertexts. Through several tests i.e. speed, correlation and autocorrelation, diffusion, and confusion tests, the simulation result showed the superiority of our algorithms over the other algorithms. For the proof of concept, the proposed algorithms have been simulated in the network simulator, where the result showed that along with the increase of the number of nodes, the throughput of the network increased, while the delay is relatively constant around 6000 ms for 20 up to 70 nodes.